Penerapan Media Card Sort untuk Meningkatkan Keterampilan Menulis Karangan Narasi Beridiom Siswa Kelas VA SDN Joglo - Liliana Maharani; Fadhil Purnama Adi; Septi Yulisetiani (Didaktika Dwija Indria, 2026)
The idiomatic narrative essay writing skills of fifth-grade students (Class VA) at SDN Joglo Surakarta were found to be relatively low, as indicated by the pre-action test results, with an average score of 55.18 and a class mastery percentage of only 29.63%, while the average score for idiom use was 65.2 with a class mastery percentage of 48.15%. This condition was caused by the picture-series media used by the teacher, which had not been able to optimally facilitate students in enriching their vocabulary and understanding the use of idioms. Based on this problem, the present study aimed to improve the idiomatic narrative essay writing skills of Class VA students at SDN Joglo Surakarta through the implementation of Card Sort learning media. This study employed a qualitative approach using the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, conducted with Class VA students during the 2025/2026 academic year across two cycles, each consisting of two meetings covering the stages of planning, action, observation, and reflection. Data were collected through interviews, observations, tests, and documentation, and were analyzed using an interactive data analysis technique, namely data reduction, data display, and conclusion drawing. The findings showed a consistent improvement across each cycle. The average score for narrative essay writing increased from 55.18 in the pre-action stage to 73.51 in Cycle I and 80.57 in Cycle II, with the class mastery percentage rising from 29.63% to 48.15% and 80.77%, respectively. The ability to use idioms in narrative essays also improved, with the average score increasing from 65.2 to 74.07 and 87.01, and the mastery percentage rising from 48.15% to 70.37% and 84.62%. Teacher performance and student engagement also showed improvement in each cycle. Based on these findings, it can be concluded that Card Sort learning media was proven effective in improving the idiomatic narrative essay writing skills of Class VA students at SDN Joglo Surakarta.